2001
DOI: 10.1001/archinte.161.4.589
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diet on Blood Pressure and Age-Related Changes in Blood Pressure in the US Population

Abstract: A diet low in sodium, alcohol, and protein is associated with lower systolic blood and pulse pressure. Potassium intake was associated with lower systolic and diastolic blood pressure, whereas alcohol intake was associated with lower diastolic blood pressure. In addition, the age-related changes in systolic blood pressure were attenuated by higher calcium and protein intakes. Magnesium was not associated with any changes in blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
81
3
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(101 citation statements)
references
References 40 publications
15
81
3
2
Order By: Relevance
“…This type of dietary assessment is widely used in international epidemiological studies. [32][33][34] The results obtained with the above-mentioned questionnaires are basically the same. Different questionnaires were used because the subjects of the THUSA BANA study (aged 10-15 years) were too young to fully understand and answer the QFFQ meaningfully.…”
supporting
confidence: 54%
“…This type of dietary assessment is widely used in international epidemiological studies. [32][33][34] The results obtained with the above-mentioned questionnaires are basically the same. Different questionnaires were used because the subjects of the THUSA BANA study (aged 10-15 years) were too young to fully understand and answer the QFFQ meaningfully.…”
supporting
confidence: 54%
“…In the Third National Health and Nutrition Examination Survey (NHANES III), a higher intake of calcium was associated with a reduced rate of rise in systolic BP with age, suggesting an effect of dietary calcium also on long-term BP control. 60 Minor reductions in population BP could have a substantial impact on cardiovascular disease in westernized societies. MacMahon et al 61 showed that a prolonged difference in usual diastolic BP of only 5 mm Hg is associated with at least 34% less stroke and 21% less coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…This type of dietary assessment is widely used in international epidemiological studies. 10,26,27 Macronutrients (protein, fat and carbohydrate) and fibre were calculated, and micronutrients (such as calcium, magnesium, sodium, potassium and phosphorus), vitamins (such as A, B 6 , B 12 , C, D, E and biotin) and cholesterol were calculated in the appropriate units, using a computer programme based on the South African food composition tables. 28 Statistical analysis All processed data were transferred to Excel and further statistically analysed by means of the software computer package STATISTICA.…”
Section: Dietary Intakementioning
confidence: 99%